Buchu (Agathosma betulina and A. crenulata): Rightfully Forgotten or Underutilized? - Brendler, Thomas; Abdel-Tawab, Mona (Frontiers in Pharmacology, 2022)
Today, the term buchu refers to the two species in commerce, Agathosma betulina and Agathosma crenulata (Rutaceae). Its traditional use in urinary tract infections and related ailments made it a popular remedy, specifically in the US, in 19th century, but with the advent of antibiotics it became largely obsolete. Recent focus is on the essential oil for use in the perfume and food-flavouring industry. A review of the scarce pharmacological research revealed moderate antimicrobial activity for a leaf extract but not the essential oil of both species in the MIC assay. In the 5-lipoxygenase (5-LO) assay the essential oil of both species revealed IC50 values of 50.37 ± 1.87 µg/mL and 59.15 ± 7.44 µg/mL, respectively. In another study 98% inhibitory activity was determined for 250 µg/mL of an ethanolic extract of A. betulina on cyclooxygenase (COX)-1 and a 25% inhibitory activity on COX-2. Analgesic activity of an ethanolic extract of A. betulina was shown in mice. Moderate antioxidant activity was determined for methanol:dichlormethane extracts of A. betulina and A. crenulata and an aqueous extract of A. betulina showed a Trolox Equivalent Antioxidant Capacity (TEAC) of 11.8 µM Trolox. Recent in vitro studies with a commercial aqueous extract of buchu revealed increased uptake of glucose added to 3T3-L1 cell line, significant inhibition of the respiratory burst of neutrophils and monocytes, reduction in the expression of adhesion molecules and inhibition of the release of IL-6 and TNF-α. In diabetic rats the ingestion of aqueous buchu extract completely normalized the glucose level and in rats receiving a high fat diet the consumption of aqueous buchu extract resulted in less weight gain and less intraperitoneal fat gain as well as reduction of elevated blood pressure to normal associated with cardioprotective effects. Limitations in the hitherto conducted research lie in the undisclosed composition of the buchu extracts used and the difficulty in extrapolating data from animal studies to humans. Health claims for buchu products need to be substantiated by randomized, double-blind and placebo-controlled studies. Only then can they be promoted for their true therapeutic potential.